PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT DESA TERHADAP PEMBANGUNAN DI DESA ALAHAN KECAMATAN ROKAN IV KOTO KABAUPATEN ROKAN HULU TAHUN 2015-2016 - Rafhi, M.; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Village Community Empowerment Institute (LPMD) is a village institution established on the initiative of the community with the aim of being able to accommodate and convey the aspirations of the village community. The role of Village Community Empowerment Institution is as a container of community aspiration to assist the village head in the process of improving the quality of society through community empowerment and simplify the existing development process in the village. Law No. 6 Year 2014 on Village Article 94 paragraph 3 "Village empowerment of village community institutions that exist in assisting the implementation of the function of governance of the Village, the implementation of village development, community development Village, and empowerment of village communities. The Alahan Village Community Empowerment Institution has not performed its role as an institution that accommodates the aspirations of the community, besides LPMD Alahan has no program of activities so that they work unsuited tupoksi. This research was conducted in October 2017 until January 2018. The purpose of this research is to know the role of Alahan Village Community Empowerment Institution 2016. The method used in this research is descriptive qualitative method, where the researcher try to explain the role of Alahan Village Community Empowerment Institution in Development. Data collection techniques in this study is to use interviewing techniques and documentation. Based on interviews to all informants and based on supporting data and information obtained by the researcher. It can be concluded that the role of Alahan Village Community Empowerment Institution in Development is not going well, because the Village Community Empowerment Board does not understand its duties and functions, so that the implementation of empowerment and development activities is not implemented by Alahan Village Community Empowerment Institution. Keywords: Role, LPMD, Village, Development